2021
DOI: 10.2147/cmar.s322195
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the lncRNA AC012213.3 Promotes Proliferation, Migration and Invasion of Breast Cancer via RAD54B/PI3K/AKT Axis and is Associated with Worse Patient Prognosis

Abstract: Background Long noncoding RNA (LncRNA) has been shown to mediate the development of human malignancies. However, data on its role in breast cancer remains scant. We aimed to evaluate the prognostic potential of lncRNAs in breast cancer. Methods We downloaded data on breast cancer patients from The Cancer Genome Atlas (TCGA) database. Tissues were obtained from The Fifth People’s Hospital of Chengdu. We then used the DESeq2 package to profile the expression of the lncRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Hongmei Zhong et al proved that lncRNA AC012213.3 was highly expressed in breast cancer tissues and cell lines. 27 In addition, they also found that RAD54B was a downstream molecule of AC012213.3, overexpression of the lncRNA AC012213.3 promoted proliferation, migration and invasion of breast cancer via RAD54B/PI3K/AKT axis and was associated with worse patient prognosis. 27 However, reports on the other two high-risk lncRNAs (YTHDF3−AS1 and AC079298.3) are scarce, which needs further study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hongmei Zhong et al proved that lncRNA AC012213.3 was highly expressed in breast cancer tissues and cell lines. 27 In addition, they also found that RAD54B was a downstream molecule of AC012213.3, overexpression of the lncRNA AC012213.3 promoted proliferation, migration and invasion of breast cancer via RAD54B/PI3K/AKT axis and was associated with worse patient prognosis. 27 However, reports on the other two high-risk lncRNAs (YTHDF3−AS1 and AC079298.3) are scarce, which needs further study.…”
Section: Discussionmentioning
confidence: 97%
“… 27 In addition, they also found that RAD54B was a downstream molecule of AC012213.3, overexpression of the lncRNA AC012213.3 promoted proliferation, migration and invasion of breast cancer via RAD54B/PI3K/AKT axis and was associated with worse patient prognosis. 27 However, reports on the other two high-risk lncRNAs (YTHDF3−AS1 and AC079298.3) are scarce, which needs further study. So far, there are few studies on ferroptosis-related lncRNAs, especially relationship between it and breast cancer needs further research, so as to find more novel therapeutic targets for breast cancer, particularly for those refractory cancer patients.…”
Section: Discussionmentioning
confidence: 97%
“…The overexpression of AC012213.3 can potentially result in enhanced proliferation of BRCA cells and BRCA cell invasion. These are realized through the promotion of the process of transcription of the downstream target gene RAD54B 26 . MAPT–IT1 is associated with Koolen-De Vries syndrome 27 and can potentially predict the prognoses of patients with BRCA 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, three genes, lncRNAs YTHDF3-AS1, AC079298.3 and AC012213.3, which are overexpressed in at-risk populations, were screened, indicating that they may be at-risk oncogenes for BC. In addition, lncRNA NC012213.3, a downstream molecule of AC012213.3, and overexpressed LncRNA AC012213.3 promotes BC multiplication, invasion and invasiveness through the RAD54B/PI3K/AKT axis and is associated with poor patient outcomes [ 193 ]. However, studies on YTHDF3-AS1 and AC079298.3 are limited and require further investigation.…”
Section: Ferroptosis-associated Lncrnas In Bcmentioning
confidence: 99%